Comparative Analysis of Amino ACID and Bioactive Peptide Profiles During Time-resolved Fermentation of Wheat and Stout Brewer's Spent Grain by Lactiplantibacillus plantarum - Ha, Minh Quoc; Juhász, Angéla; Santoso, Teguh; Nye-Wood, Mitchell G; Berthevas, Mathilde; Zhao, Zhiyu; Kitundu, Eileen; Chen, Tony; Colgrave, Michelle L; Le, Thao T (Elsevier, 2026)
Brewers’ spent grain (BSG), a protein- and fibre-rich brewing by-product, contains bioactive compounds, yet techniques to fully recover and utilise these bioactive fractions remain underdeveloped. This study investigated the proteolytic transformation of two BSG types, non-roasted wheat and roasted stout BSG, during 10 days of fermentation with Lactiplantibacillus plantarum. Discovery and targeted LC-MS/MS proteomics were used to characterise protein abundance, peptide release, and free amino acid profiles throughout fermentation. Proteomic analysis identified 503 proteins in wheat BSG and 347 in stout BSG. Wheat BSG generated higher peptide diversity than stout BSG (1,227 vs. 436 peptides), with peptide peaking on Day 4, whereas stout BSG showed delayed peptide release, primarily during Days 7–9, indicating substrate-dependent proteolytic dynamics. Targeted quantification of 28 peptides revealed distinct temporal patterns for predicted antimicrobial and antihypertensive activities. Antimicrobial peptides peaked during mid-fermentation in both BSG types, while antihypertensive peptides peaked earlier in wheat BSG and later in stout BSG. Peptides containing partial wheat allergy and coeliac disease-related epitope motifs were detected predominantly in wheat BSG and accumulated throughout fermentation, whereas such motifs were largely absent in stout BSG. This suggests that intensive thermal processing associated with stout production may reduce the prevalence of safety-relevant epitope-containing protein regions. Free amino acid profiling revealed higher hydrophobic amino acid concentrations in stout BSG (0.98 vs. 0.61 mg/100 g protein) and charge-related inter-substrate differences. These findings demonstrate that BSG type strongly influences proteolytic outcomes and support substrate-specific fermentation strategies for the targeted and safe valorisation of brewing by-products.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 3004 Crop and Pasture Production; 3006 Food Sciences; 3004 Crop and pasture production; Brewers’ spent grain; Lactiplantibacillus plantarum; Peptide profiling; Food allergen epitopes; Bioactive peptides